Effect of replacement of concentrate mixture with a multi-nutrient liquid supplement on perfomance of bufflao heifers - ANKITA, ANKITA; VERMA, A K; SINGH, P; DAS, A; GAUR, G K (The Indian Journal of Animal Sciences, 2016)
The primary objective of this experiment was to study the effect of replacement of concentrate mixture with molasses based multi-nutrient liquid supplements that contained either 2 (MMLS) or 4% mineral mixture (MMLS plus) on performance of buffalo heifers. Female Murrah buffalo heifers (18),12 to 14 months of age and weighing 290±2 kg were randomly distributed into 3 groups of 6 each in an experiment based on randomized block design. All animals were supplied with green forages (2 kg DM/d) and wheat straw ad lib. In addition, animals in group T1 (control) were fed a concentrate mixture to meet their nutrient requirements. However, 20% of the concentrates were replaced with MMLS and MMLS plus in groups T2 and T3, respectively. Digestibility of NDF and hemicelluloses was higher in T3 as compared to T2 and control. Digestibility of other nutrients, excretion of purine derivatives and growth performance were comparable among the groups. It was concluded that multi-nutrient liquid supplements can safely replace 20% concentrate mixture without any adverse effect on nutrient utilization and growth performance of buffalo heifers.